2007
DOI: 10.2172/929209
|View full text |Cite
|
Sign up to set email alerts
|

Using Carbon Dioxide to Enhance Recovery of Methane from Gas Hydrate Reservoirs: Final Summary Report

Abstract: Executive SummaryAlthough recent estimates (MILKOV et al., 2003) put the global accumulations of natural gas hydrate at 3,000 to 5,000 trillion cubic meters (TCM), compared against 440 TCM estimated (COLLETT, 2004) for conventional natural gas accumulations, how much gas could be produced from these vast natural gas hydrate deposits remains speculative. What is needed to convert these gas-hydrate accumulations to recoverable reserves are technological innovations, sparked through sustained scientific researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
(20 reference statements)
0
15
0
Order By: Relevance
“… Numbers in parentheses are sources as follows: 1, Lu et al [2009]; 2, Waite et al [2009]; 3, McGrail et al [2007]; 4, this study, equation (7); 5, Kang et al [2005]; 6, Lenormand et al [1988]; 7, Donnelly and Katz [1954]; 8, Span and Wagner [1996] and Trusler and Zarari [1992]; 9, this study, section 4, Figure 4; 10, this study, equation (8); 11, Kleinberg et al [2003]; 12, Kneafsey and Pruess [2010]. …”
Section: Analysis: Sediment Scale Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“… Numbers in parentheses are sources as follows: 1, Lu et al [2009]; 2, Waite et al [2009]; 3, McGrail et al [2007]; 4, this study, equation (7); 5, Kang et al [2005]; 6, Lenormand et al [1988]; 7, Donnelly and Katz [1954]; 8, Span and Wagner [1996] and Trusler and Zarari [1992]; 9, this study, section 4, Figure 4; 10, this study, equation (8); 11, Kleinberg et al [2003]; 12, Kneafsey and Pruess [2010]. …”
Section: Analysis: Sediment Scale Implicationsmentioning
confidence: 99%
“…Methane can be recovered from hydrate‐bearing sediments by depressurization, heating or chemical injection. In particular, the injection of carbon dioxide, CO 2 , into hydrate‐bearing sediments can liberate methane, CH 4 , and sequester CO 2 in hydrate form [ McGrail et al , 2007; Ota et al , 2005a; Stevens et al , 2008; Svandal et al , 2006; Zhou et al , 2008a]. …”
Section: Introductionmentioning
confidence: 99%
“…Published theoretical studies and laboratory-scale experiments have shown the successful release of CH 4 as a result of the replacement reaction caused by CO 2 injection (Hirohama et al, 1996;Kvamme et al, 2007;Lee et al, 2003;McGrail et al, 2007;Tegze et al, 2007). Pore scale phenomena include heat release and diffusion controlled reactions, dissolution of fluid phases, gas production, and porefluid volume expansion (note: a comprehensive review of phenomena relevant to CH 4 -CO 2 replacement can be found in Jung et al (2010)).…”
Section: Introductionmentioning
confidence: 99%
“…The injection of CO 2 into CH 4 hydrate-bearing sediments has the advantage of liberating CH 4 while simultaneously sequestering CO 2 leading to the more sustainable use of a fossil fuel [McGrail et al, 2007;Ota et al, 2005;Stevens et al, 2008;Svandal et al, 2006;Zhou et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have observed no apparent dissociation during replacement [Stevens et al, 2008], and have monitored replacement ratios and rates which show that the CH 4 -CO 2 replacement rate increases near the CH 4 hydrate phase boundary and with increasing CO 2 gas pressure, reaching a constant value when the CO 2 liquefies [McGrail et al, 2007;Ota et al, 2005Ota et al, , 2007. The replacement ratio increases when a mixture of CO 2 and N 2 is used for replacement because the smaller N 2 molecule facilitates the replacement of CH 4 from the small cage in structure I hydrate [Park et al, 2006].…”
Section: Introductionmentioning
confidence: 99%